2019
DOI: 10.4028/www.scientific.net/kem.801.377
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Geopolymer Concrete Containing Recycled Plastic Beads

Abstract: Utilizing recycled plastic beads (RPB) as lightweight waste aggregates in the concrete and geopolymer application is quite attractive. This study presented the mechanical behavior, density, porosity, water absorption, abrasion resistance, thermal conductivity, and ultrasonic pulse velocity (UPV) of geopolymer lightweight concrete containing RPB. River sand in each mixture was replaced by various proportions of RPB ranging between 0-100% by weight. Sodium hydroxide concentration of 15 M, activator solution to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Zhu et al studied the thermal properties of recycled aggregate concrete and RBs and also found that the thermal conductivity of recycled aggregate concrete increases with the increase in concrete density. Wongkvanklom et al also found that the thermal conductivity coefficient increased with the increasing density of lightweight geopolymer concrete containing recycled plastic beads. The relationship between the dry density and the thermal conductivity of PRGCs in the study is plotted in Figure .…”
Section: Resultsmentioning
confidence: 92%
“…Zhu et al studied the thermal properties of recycled aggregate concrete and RBs and also found that the thermal conductivity of recycled aggregate concrete increases with the increase in concrete density. Wongkvanklom et al also found that the thermal conductivity coefficient increased with the increasing density of lightweight geopolymer concrete containing recycled plastic beads. The relationship between the dry density and the thermal conductivity of PRGCs in the study is plotted in Figure .…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the TSS of 1. 5-2.6 MPa was reported by 25 in their study on LWGPC which was produced utilizing recycled plastic beads as lightweight aggregate.…”
Section: Tensile Splitting Strengthmentioning
confidence: 82%
“…High-calcium fy ash (FA) from the Mae Moh power plant has been utilized as a precursor for AAB production in Tailand due to its extensive availability and acceptable chemical composition [19]. Te reaction between SiO 2 and CaO in the FA system assisted in the geopolymerization process when cured at room temperature [20][21][22]. Hence, a combination of C-S-H (calcium silicate hydrate) and/or C-A-S-H (calcium aluminosilicate hydrate) and N-A-S-H (sodium aluminosilicate hydrate) gels is the main reaction of the high-calcium AAB system [15,23,24].…”
Section: Introductionmentioning
confidence: 99%